A study of drag force on different type of airfoil in a subsonic wind tunnel - Muhamad Faruqi, Zahari (2013)
There had been a number of researches that investigated on drag force of airfoil in subsonic wind tunnel. This study was then conducted in order to identify drag force in subsonic wind tunnel using Computational Fluid Dynamics (CFD) software. Specifically, this research aimed to identify the drag force on ten different types NACA airfoil. NACA 0006, NACA 0009, NACA 0015, NACA 1408, NACA 1410, NACA 2408, NACA 2418, NACA 4424, NACA 6409 and NACA 6412 airfoil geometry profiles and its coordinates were generated from a NACA 4 Digits Series Generator and then designed by using ANSYS (Fluent) geometry and computed using ANSYS 14.0 software , these Computational Fluid Dynamic was used to simulate the external flow analysis on the airfoils and then the prediction of the drag force validate its simulation result with experimental result of drag force in subsonic wind tunnel. Nonetheless, the boundary condition was operated at a nominal velocity 17 m/s during the coefficient measurements, a Reynolds's number of about 1,163,798. The airfoil, with a one meter chord, was analyzed at zero degree angles of attack. Moreover, the result show NACA 4424 that have highest drag force and NACA 0006 have the lowest drag force at same boundary condition. Furthermore, the drag was generated was too small to make any significant change to the airfoil performance.